Use of a human embryonic stem cell model to discover GABRP, WFDC2, VTCN1 and ACTC1 as markers of early first trimester human trophoblast. (2nd May 2020) - Karvas, Rowan M; McInturf, Samuel; Zhou, Jie; Ezashi, Toshihiko; Schust, Danny J; Roberts, R Michael; Schulz, Laura C
Abstract: Human placental development during early pregnancy is poorly understood. Many conceptuses are lost at this stage. It is thought that preeclampsia, intrauterine growth restriction and other placental syndromes that manifest later in pregnancy may originate early in placentation. Thus, there is a need for models of early human placental development. Treating human embryonic stem cells (hESCs) with BMP4 (bone morphogenic protein 4) plus A83-01 (ACTIVIN/NODAL signaling inhibitor) and PD173074 (fibroblast growth factor 2 or FGF2 signaling inhibitor) (BAP conditions) induces differentiation to the trophoblast lineage (hESCBAP ), but it is not clear which stage of trophoblast differentiation these cells resemble. Here, comparison of the hESCBAP transcriptome to those of trophoblasts from human blastocysts, trophoblast stem cells and placentas collected in the first–third trimester of pregnancy by principal component analysis suggests that hESC after 8 days BAP treatment most resemble first trimester syncytiotrophoblasts. To further test this hypothesis, transcripts were identified that are expressed in hESCBAP but not in cultures of trophoblasts isolated from term placentas. Proteins encoded by four genes, GABRP (gamma-aminobutyric acid type A receptor subunit Pi), WFDC2 (WAP four-disulfide core domain 2), VTCN1 (V-set domain containing T-cell activation inhibitor 1) and ACTC1 (actin alpha cardiac muscle 1), immunolocalized to placentas at 4–9 weeks gestation, and their expression declined with gestational age ( R 2 = 0.61–0.83). None are present at term. Expression was largely localized to syncytiotrophoblast of both hESCBAP cells and placental material from early pregnancy. WFDC2, VTCN1 and ACTC1 have not previously been described in placenta. These results support the hypothesis that hESCBAP represent human trophoblast analogous to that of early first trimester and are a tool for discovery of factors important to this stage of placentation.